A prospective study of epidemiology and clinical presentation of non-traumatic acute abdomen cases in a tertiary care hospital of central India - Jain, Rajiv; Gupta, Vikas (International Surgery Journal, 2016)
Background:Acute Abdomen is a term used to encompass a spectrum of surgical, medical and gynecological conditions ranging from trivial to life threatening conditions, which require hospital admission, investigations and treatment. The purpose of this study was to identify the epidemiological pattern and to determine the spectrum of disease causing “non-traumatic acute abdomen in central India”. Methods: This is a prospective study of 98 patients of non-traumatic acute abdominal cases conducted in the Department of Surgery, Sri Aurobindo Medical College and PG Institute, Indore, Madhya Pradesh, India. In this study, preoperative detailed history and thorough physical examination was done for all acute abdominal emergencies, to arrive at pre-operative diagnosis. Results:Amongst the study of 98 patients, males have higher incidence of acute abdomen with the young age group (21-30 years) most commonly affected. Perforation peritonitis constituted the most common cause of acute abdomen (39.7%), followed by acute appendicitis (37.7%), followed by intestinal obstruction (14.2%). Conclusions: This study was conducted to evaluate the epidemiology, etiology and differential diagnosis of non-traumatic acute abdomen. At the end of the study, we had a better insight of the spectrum of the condition and we concluded that there is more scope for further work in the same field for better understanding of this topic.